2018
DOI: 10.1177/1044207318792178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Self-Determined Learning Model of Instruction on Self-Determination and Goal Attainment in Adolescents With Intellectual Disability

Abstract: The Self-Determined Learning Model of Instruction (SDLMI) is an evidence-based practice designed to enable teachers to teach students to self-regulate problem solving to set and attain educationally relevant goals. This study reports on findings and outcomes of the first year of a statewide implementation of the SDLMI by teachers working with students with intellectual disability to promote skills, knowledge, and beliefs that will lead to opportunities for meaningful, integrated employment. Data are reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 29 publications
(39 reference statements)
1
61
0
1
Order By: Relevance
“…It is unclear what level of fidelity of implementation is needed to enhance outcomes, although this study documents that there is a relationship. We have repeatedly asserted that fidelity ratings on the SDLMI Teacher Fidelity Measure in the average range are acceptable (Shogren et al, 2019)-as found in this study-given the complexity of the SDLMI. Other research on implementation fidelity suggests that 100% or "perfect" fidelity is not a reasonable expectation, or a necessity to affect outcomes (Durlak & DuPre, 2008;Harn, Parisi, & Stoolmiller, 2013).…”
Section: Implications For Research and Practicesupporting
confidence: 65%
See 1 more Smart Citation
“…It is unclear what level of fidelity of implementation is needed to enhance outcomes, although this study documents that there is a relationship. We have repeatedly asserted that fidelity ratings on the SDLMI Teacher Fidelity Measure in the average range are acceptable (Shogren et al, 2019)-as found in this study-given the complexity of the SDLMI. Other research on implementation fidelity suggests that 100% or "perfect" fidelity is not a reasonable expectation, or a necessity to affect outcomes (Durlak & DuPre, 2008;Harn, Parisi, & Stoolmiller, 2013).…”
Section: Implications For Research and Practicesupporting
confidence: 65%
“…However, questions about implementation and scaling-up of the SDLMI remain, particularly in terms of supports needed by teachers to sustain the SDLMI as a part of ongoing instruction over time and as other interventions are introduced. Researchers have begun to define and examine the impact of an SDLMI coaching model (Hagiwara, Shogren, Lane, Raley, & Smith, in press; Shogren et al, 2019) as well as online supports or online plus coaching supports for implementation of the SDLMI (Shogren, Wehmeyer, Lane, & Quirk, 2017) to explore the impact of these factors on adoption. Although research has generally suggested adequate fidelity of implementation in large-scale studies (Burke, Shogren, Antosh, LaPlante, & Masterson, 2019; Shogren, Raley, et al, 2018), less is known about how teachers perceive their ability to implement the SDLMI with fidelity, and the degree to which these perceptions are stable over time and/or shaped by the introduction of other intervention and instructional demands.…”
mentioning
confidence: 99%
“…Powers et al (2012) had similar results in school and post-school using an intervention to promote self-determination called My Life for youth in foster care and special education. Shogren, Burke, et al (2017) reported the results of a state-wide implementation of the SDLMI with transition-age youth planning for the movement from school to integrated employment, and found that one year of implementation of the SDLMI teacher's perceptions of adolescent self-determination and transition-related goal attainment.…”
Section: Interventions To Promote Self-determination and Post-schoolmentioning
confidence: 99%
“…Rather than teaching specific transition planning and self-determination skills, it is used by educators to shape their instruction to be student directed rather than teacher directed by supporting students to self-regulate problem solving leading to goal setting and attainment in any content area, including planning for the transition to employment (Shogren et al, 2018). The importance of the SDLMI is that it can be used by teachers with students with a range of support needs, including students with the most SCDs (Shogren et al, 2019) by individualizing the supports based on students’ communication and comprehension skills. Researchers have established the casual impact of the SDLMI on transition goal attainment by students with an intellectual disability (Shogren et al, 2012).…”
Section: Discussionmentioning
confidence: 99%